(untitled) - Matthias, Catherine (Childrens Press, 1984)
Simple text and illustrations describe some of the duties of a police officer.
"Prepared under the direction of Robert Hillerich, Ph.D."
Includes index.
Keywords: Police; Juvenile literature; Police; Police; Juvenile literature; Occupations